2005
DOI: 10.1016/j.sysconle.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A note on persistency of excitation

Abstract: We prove that if a component of the response signal of a controllable linear time-invariant system is persistently exciting of sufficiently high order, then the windows of the signal span the full system behavior. This is then applied to obtain conditions under which the state trajectory of a state representation spans the whole state space. The related question of when the matrix formed from a state sequence has linearly independent rows from the matrix formed from an input sequence and a finite number of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
210
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 606 publications
(266 citation statements)
references
References 10 publications
2
210
0
Order By: Relevance
“…The model-free method of (Markovsky 2015) is a subspace-type method (Van Overschee and De Moor 1996b) for solving the autonomous identification problem in Section 3.3, however, it estimates directly the parameter of interestū. Assuming that ∆y is persistently exciting of sufficiently high order (Willems et al 2005), we have that the most powerful unfalsified model B mpum (∆y) of ∆y is the system ∆B. Since, by definition,…”
Section: Model-free Methods Of (Markovsky 2015)mentioning
confidence: 99%
See 1 more Smart Citation
“…The model-free method of (Markovsky 2015) is a subspace-type method (Van Overschee and De Moor 1996b) for solving the autonomous identification problem in Section 3.3, however, it estimates directly the parameter of interestū. Assuming that ∆y is persistently exciting of sufficiently high order (Willems et al 2005), we have that the most powerful unfalsified model B mpum (∆y) of ∆y is the system ∆B. Since, by definition,…”
Section: Model-free Methods Of (Markovsky 2015)mentioning
confidence: 99%
“…In the case of exact measurements, 2n + 1 data points are sufficient to identify the system exactly (Willems et al 2005). In the case of noisy data, the convergence rate of the parameters depends on the algorithm and the measurement process.…”
mentioning
confidence: 99%
“…From Proposition 6 it follows that every column of the matrix F, computed on step 2 of Algorithm 2, is a free response of B. Moreover, from (Willems et al 2005, Corollary 2) and the assumption T r ≥ l(B) it follows that rank(F) = n(B). The statement of the proposition follows from rank(O) = rank(F) = n(B).…”
Section: Special Case U = 0: Zero Input Responsementioning
confidence: 91%
“…In Corollary 2 of Willems, Rapisarda, Markovsky, and De Moor (2005), it has been shown that, for every trajectory (u, x) of a statespace system σ x = Ax + Bu with n-dimensional state vector x and m-dimensional input u, it holds that u p.e. of order n ⇒ rank…”
Section: Noise-free Identificationmentioning
confidence: 99%